The Unconscious, Drive, and Desire in Anglo-Saxon Philosophy and Psychoanalysis - De la Puente Arbaiza, Carlos Alberto (2021)
This work explores the reception of Psychoanalytic ideas by anglo- saxon philosophy, the latter represented by Bertrand Russell, John Dewey, Ludwig Wittgenstein, Stanley and Marcia Cavell, Donald Davidson, Richard Rorty and David Finkelstein. I also include Jurgen Habermas´ interpretation of Freud´s ideas under the label of Anglo Saxon Philosophy. The first part is dedicated to the concept of desire in Psychoanalysis and in anglo-saxon philosophy. In the second part, deals with the concept of Unconscious.